Cost-effectiveness of palbociclib plus fulvestrant as second-line therapy of women with HR+/HER2- advanced breast cancer - A Chinese healthcare system perspective - Zhu, Wentao; Zheng, Miaomiao; Xia, Panpan; Hong, Wanglong; Ma, Guoqiang; Shen, Aizong (Frontiers in Oncology, 2023)
Aim To evaluate the cost-effectiveness of palbociclib plus fulvestrant in the second-line treatment of women with hormone receptor-positive and human epidermal growth factor receptor 2-negative advanced breast cancer based on the latest published follow-up data from the perspective of the Chinese healthcare system. Methods In view of the PALOMA-3 trial, a Markov model was built for this purpose, which included three health states: progression-free survival (PFS), progressed disease (PD), and death. The cost and health utilities were mainly derived from the published literature. One-way sensitivity analysis and probabilistic sensitivity analysis were carried out to verify the robustness of the model. Results In the base case analysis, compared with the placebo plus fulvestrant arm, the palbociclib plus fulvestrant arm yielded an additional 0.65 quality-adjusted life years (QALYs) (2.56 QALYs vs. 1.90 QALYs) with an incremental cost of $36,139.94 ($55,482.06 vs. $19,342.12), resulting an incremental cost-effectiveness ratio (ICER) of $55,224.90/QALY, which was deeply higher than a willingness-to-pay (WTP) threshold of $34,138.28 per QALY in China. The results of one-way sensitivity analysis indicated that the utility of PFS, cost of palbociclib, and cost of neutropenia had a great influence on the ICER. Conclusions Palbociclib plus fulvestrant is unlikely to be cost-effective in comparison with placebo plus fulvestrant as second-line therapy of women with HR+/HER2- advanced breast cancer.